Stable fixation of a madreporic Lord femoral prosthesis at 31-year follow-up in a total hip arthroplasty: A case report - Judas, Fernando M. (2016)
INTRODUCTION: Lord total hip prosthesis was discontinued due to high revision rates of the smooththreaded acetabular component and negative effects of stress shielding in the proximal femur.PRESENTATION OF CASE: We report the outcome of a Lord cementless femoral stem, in a 55-year-oldwoman. In 1984, the patient underwent a Lord total hip arthroplasty for the treatment of advanced dys-plastic osteoarthritis of the left hip. After 12 years, the cementless acetabular component of the prosthesishad been revised due to aseptic loosening. An acetabular metallic support ring and a cemented polyethy-lene cup were implanted, the femoral stem was not changed. The acetabular bone loss was reconstructedwith morsellised cancellous bone allografts by the impacting technique. No complications were reportedduring the period of 19 years of the postoperative course. At the last clinical and radiological evaluations,the patient presented an asymptomatic hip and expressed high degree of satisfaction with the surgeryresult. The femoral stem was stable, with no measurable subsidence or radiolucent lines around the stem.DISCUSSION: Several reports have presented a high clinical success rate with the fully-porous-coated Lordfemoral stem in both primary and revision cases. However, the long-term results showed a substantialrate of proximal femoral bone loss and thigh pain.CONCLUSION: In our case, the Lord stem showed an excellent long-term result at the 31-year follow-up. To our knowledge, there is no published report with results of the Lord stem longer than 26-year’sfollow-up.